A sensitivity analysis of the effect of curvature ratio on the thermal-hydraulic performance in helically coiled tubes with corrugated walls - Kirkar, Safak Metin; Gonul, Alisan; Dalkilic, Ahmet Selim (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2023)
To enhance thermal-hydraulic performance by rising the heat transfer rate with reasonable pressure loss, heat transfer augmentation methods should be considered in the heat exchanger designs. The use of two distinct passive heat transfer augmentation methods, helically coiled tube structure and helically corrugated tube wall, is considered in this study to investigate numerically the effect of coil diameter on the heat transfer and flow characteristics of single-phase liquid water flowing in the corrugated coiled tubes. Curvature ratio, the ratio of tube-to-coil diameter, and the use of corrugation are one of the most influential factors on heat transfer in coiled tubes due to their contributions to the formation of secondary and swirl flows. The curvature ratios between 0.0958 and 0.2875 are considered for smooth and equivalent corrugated coiled tubes with the same tube diameter of 5.75 mm and length of 390 mm. In all simulations, the water flows through the investigated tubes at Dean numbers between 150 and 3270 under boundary conditions of uniform surface heat flux. The influence of coil diameter on Nusselt number, friction factor, and thermal-hydraulic performance is examined by a com-mercial software. As a result, the enhancement in the thermal-hydraulic performance of corrugated coiled tubes compared to smooth straight ones is much higher, up to 270%, at Reynolds numbers below 2300 than those at higher Reynolds numbers. Additionally, the Genetic Aggregation Response Surface Methodology for the esti-mation of output parameters and their sensitivity analysis is employed by evaluating the Reynolds number and curvature ratio as inputs, and Nusselt number, friction factor, and performance evaluation criteria as outputs. Finally, the output parameters are estimated with an error range of +/- 5%, and the Reynolds number on Nusselt number and performance evaluation criteria, and curvature ratio on friction factor are realized to be more effective.
Keywords: Curvature ratio; Corrugation; Helically coiled tube; Performance evaluation criteria; Sensitivity analysis; CONVECTIVE HEAT-TRANSFER; TRANSFER ENHANCEMENT; TURBULENT-FLOW; PRESSURE-DROP; EXCHANGER; LAMINAR; Thermodynamics; Engineering